Changing meanings: the Ghanaian memorial stool of the KwaZulu-Natal Museum - Dominy, G. (Southern African Humanities, 2017)
This article examines the historical context in which the so-called ‘Ashanti Golden Stool’ was acquired as an iconic artefact for the new Natal Museum in the first decade of the 20th century, the heyday of imperialism. The multi-layered symbolism surrounding the stool and the importance of chiefly stools as symbols of authority in Ghana are explored. The role of the donor, Sir Matthew Nathan, governor of Natal and former governor of the Gold Coast (Ghana), in obtaining the stool and the West African collection for the museum is discussed in the context of inter-colonial imperialism. The history of the memorial stool provides a case study for historians examining artefacts of material culture as sources of historical knowledge.